Towards an integral analysis of stereotypes: Challenging the standard guarantee of impartiality Hacia un análisis integral de estereotipos: Desafiando la garantía estándar de imparcialidad - Clérico, Laura (Revista Derecho del Estado, 2018)
The use of stereotypes to the detriment of the discriminated group should imply questioning the standard guarantee of judicial impartiality. Even taking the analysis of stereotypes seriously, the depth of its consequences has not been sufficiently taken into account in the constitutional and human rights argumentation because it has not challenged with all intensity the standard way in which the guarantee of impartiality is conceived and applied in legal practice and even by the regional court for the protection of human rights. I will defend two central theses: (1) the use of stereotypes necessarily impacts on the analysis of the guarantee of impartiality and (2) impartiality must get rid of the presumption of impartiality.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Argumentation in constitutional law and human rights; Gender; Impartiality; Stereotypes; Structural inequality